Mechanisms of circular RNA circ_0066147 on pancreatic cancer progression - Zhang Jie (De Gruyter, 2021)
The purpose of the study was to explore the precise parts of circ_0066147 (circular RNA [circRNA] scm-like with four mbt domains 1, circSFMBT1) in pancreatic cancer (PC) progression.